Russian Religious Non-Conformism in the Late 19th and Early 20th Centuries: Baptists and Evangelical Christians in the Urals - Glavatskaya, Elena; Popova, Nadezhda (Quaestio Rossica, 2016)
The article focuses on Russian religious non-conformists (Baptists and Evangelical Christians) from the late 19th century until 1929. The research is based on the analysis of various historical, archival, and personal sources, as well as oral and printed sources, photographs and legislation, and the First Russian Census of 1897. The authors also collected materials during field research among the Yekaterinburg Baptists in 2014–15 (field materials from N. Yu. Popova’s archive) and used documents from the personal archive of Yekaterinburg’s Baptist community leader P. D. Yakovlev. As a result, they managed to define the dynamics of Baptist and Evangelical Christian growth and distribution in the Urals and to demonstrate their ethnic and gender composition and literacy level. The article shows that the Evangelical movement started to develop in the Central Urals later than in other regions of Russia and embraced ethnic Russians with a relatively high level of literacy. This could be because of the Central Urals’ special status as a mining and metal producing region that did not play host to exiles. In addition, it was one of the strongholds of the Old Believers, the representatives of an older form of Russian nonconformity. Yekaterinburg was the centre of religious non-conformists in the Urals and had the largest Baptist congregation in the region by the end of the 1920s. The Ural Evangelical movement developed in the same way as in Europe, attracting socially active and mobile urban youth and women. The authors argue that, although it was in opposition to the Orthodox Church, the Evangelical movement presented no danger to the state, but rather contributed to the development of civil society in late 19th- and early 20th-century Russia.